Tissue-infiltrating lymphocytes signature predicts survival in patients with early/intermediate stage hepatocellular carcinoma - Tian, Meng-Xin; Liu, Wei-Ren; Wang, Han; Zhou, Yu-Fu; Jin, Lei; Jiang, Xi-Fei; Tao, Chen-Yang; Tang, Zheng; Zhou, Pei-Yun; Fang, Yuan; Qu, Wei-Feng; Ding, Zhen-Bin; et al. (BMC medicine, 2019)
Intratumoral immune infiltrates have manifested a robust prognostic signature in patients with hepatocellular carcinoma (HCC). We hypothesized that a novel tissue-related immune signature (TRIS) could improve the prediction of postoperative survival for patients diagnosed with early/intermediate HCC. Twenty-eight immune features were immunohistochemically examined on 352 HCC specimens. The LASSO Cox regression model was used to construct a five-feature-based TRIS. The univariate and multivariate Cox analyses were performed. Based on independent predictors, the immune-clinical prognostic index (ICPI) was established. Performance assessment was measured with C-index and compared with seven traditional staging systems. The independent validation cohort (n = 393) was included to validate the model. By using the LASSO method, the TRIS were constructed on the basis of five immune features, CD3 , CD27 , CD68 , CD103 , and PD1 . Multivariate Cox analysis showed that the TRIS was an independent prognostic predictor. In the training cohort, γ-glutamyl transferase, tumor diameter, tumor differentiation, and TRIS were incorporated into the ICPI. The ICPI presented satisfactory discrimination ability, with C-index values of 0.691 and 0.686 in the training and validation cohorts, respectively. Compared with seven conventional staging systems (C-index, training cohort, 0.548-0.597; validation cohort, 0.519-0.610), the ICPI exhibited better performance for early/intermediate-stage HCCs. Further, the patients were categorized into three subgroups with X-tile software, and the stratified ICPI presented a superior corrected Akaike information criterion and homogeneity in both cohorts. Our ICPI was a useful and reliable prognostic tool which may offer good individualized prediction capability for HCC patients with early/intermediate stage.